Prospectiva estratégica para análise da interação entre os programas e variáveis relacionadas aos restaurantes populares: um estudo de caso no município de Toledo - Zanini, Elaine de Oliveira (2016)
This study aimed to verify the interaction between programs and variables related to popular restaurants in the city of Toledo / PR is responsible for its good performance factor in the city of Toledo, this performance demonstrated by the large number of feasible units in the city. In the first stage of the research the Delphi technique was used to select respondents, the programs and the variables used in the analysis, then the prospective structural analysis was chosen to analyze the data, with support from MICMAC software. As a result, we highlight the identification of key variables and drive system programs, which deserve greater attention. Another result was the variable "Family Farmers' as the driving of the whole system. One can also identify the qualified technical team failed joints that have brought positive results for the program. In addition, the popular restaurants in Toledo were designed to serve the population as a whole and not just the people in vulnerable situations, a fact that generated greater acceptance by the population. The hypothesis of this study, which is the idea that you have made possible many popular restaurants in Toledo because of programs interaction action by the municipal manager for the system studied this interaction is very strong, showing that Toledo has the highest number of popular restaurants in the state due to the action of interaction of local, state and federal programs and other variables, becoming a national reference.